Second hand smoking and tobacco use among pregnant women in Yatinuwara Medical Officer of Health (MOH) area in Sri Lanka - Ann Shanali Perera; Rasika Manori Jayasinghe; Anura Rajapakse; Ratnayake Mudiyanselage Himali Erandathie Ratnayake; Ruwan Duminda Jayasinghe (Elsevier, 2021)
This study was aimed to assess the prevalence and factors associated with second hand smoking (SHS) and tobacco use among pregnant women in Yatinuwara Medical Officer of Health area in Kandy district, Sri Lanka. This was a descriptive cross-sectional study using 390 pregnant women. Data were collected through a pre-tested, self-administered questionnaire. Fifty-four-point four percent were exposed to the SHS. Prevalence of smoking during pregnancy was 0.5% and eight women used smokeless tobacco (SLT). SHS was significantly associated with the age of the mother and family income. Women's age, monthly income, husband's education, husband's occupation, women's age at marriage and trimester of pregnancy were significantly associated with tobacco use. In conclusions, prevalence of SHS was high but tobacco use was low in pregnant women. An effective training program should be designed to educate pregnant women as well as their husbands on adverse effects of tobacco use and SHS during pregnancy.